Factors associated with an unfavorable clinical course in hospitalized patients with pelvic inflammatory disease: a retrospective cohort study of 117 patients from a Japanese academic institution - Naoko Matsuda; Seung Chik Jwa; Saki Tamura; Hiroyuki Suzuki; Masashi Takamura; Akira Namba; Takeshi Kajihara; Ryugo Okagaki; Yoshimasa Kamei; Osamu Ishihara (BMC Women's Health, 2022)
Abstract Background This study aimed to determine the factors associated with an unfavorable clinical course (emergency surgery and/or prolonged hospitalization) in patients requiring hospitalization owing to pelvic inflammatory disease (PID). Methods A retrospective study was performed on 117 patients diagnosed with PID who were admitted to our hospital between January 2014 and December 2018. Multivariate regression analysis was conducted to determine the factors associated with emergency surgical intervention, and prolonged hospitalization in a subgroup of successful expectant management (n = 93). Results The average age (mean ± standard deviation) of the patients was 41.2 ± 12.5 years; 16 (13.7%) were postmenopausal; 81 patients (69.2%) complicated with a tubo-ovarian abscess (TOA) of which 59 (72.9%) had an ovarian endometrioma; and 19 patients (16.2%) had a history of various intrauterine manipulations. Emergency surgery was performed in 24 patients (20.5%), and patients with TOA underwent emergency surgery more often than did patients without TOA (25.9% vs. 8.3%, p = 0.03), and TOA was associated with longer length of hospital stay (17.1 days vs. 8.0 days, p = 0.01). Smoking, postmenopausal status, past medical history of PID, and high C-reactive protein (CRP) level at admission were significantly associated with emergency surgery. In patients with successful expectant management, obesity (body mass index ≥ 30) and high WBC and CRP level at admission were significantly associated with prolonged hospitalization. Conclusions Of the patients requiring hospitalization owing to PID, TOA was associated with both emergency surgery and prolonged hospital stay. Patients with increased inflammatory markers and obesity should be considered to be at a high risk for unfavorable clinical course in the management of PID.